What can weighted clique graphs tell us about graph classes? - Bonomo-Braberman, Flavia (Cadernos do IME - Série Informática, 2022)
In this paper, I will briefly survey the joint work with Jayme on weighted clique graphs, and how they are a tool to characterize graph classes.